Effectiveness of Lavender Aromatherapy Administration on Insertion Pain in Hemodialysis Patients - Risma Ayu Putri Diani; Endrat Kartiko Utomo; Marni Marni; Mahjanah Hussein (Universitas Duta Bangsa Surakarta, 2026)
Insertion pain is a significant problem for hemodialysis patients that can reduce comfort and therapy compliance. Non-pharmacological interventions are needed. This study aims to analyze the effectiveness of lavender aromatherapy to reduce insertion pain in hemodialysis patients at RSUD Ir. Soekarno Sukoharjo. This study method is a randomized controlled trial with a pretest-posttest control group design. The sample consisted of 40 respondents selected through purposive sampling and divided into intervention groups (n=20) and control groups (n=20). The intervention group received lavender aromatherapy inhalation for 5-10 minutes before insertion. The pain scale was measured using the Wilcoxon and Mann-Whitney tests. The results showed that before the intervention, the average pain score of both groups was in the moderate category (intervention=4.45, control=4.35). After the intervention, the pain score of the intervention group decreased significantly to 2.55 (mild pain), while the control group remained at 4.40 (moderate pain). Statistical tests showed a very significant difference between the groups (p=0.000). Cohen's results (2.44) confirmed the influence of the intervention in the large effect size category. In conclusion, lavender aromatherapy was proven to be very effective in reducing insertion pain in hemodialysis patients and is recommended as a complementary therapy.